LEADERSHIP OF SCHOOL ADMINISTRATORS AND HAPPINESS OF WORKING IN SCHOOL UNDER RATCHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Thongdee, Amornrat; Dejbamrung, Somchai; Dejbamrung, Sombat; Surasacron, Wirot; Jammuang, Jamjuree (Journal of MCU Nakhondhat, 2024)
The purposes of this research were to study, 1) The leadership of school administrators under Ratchaburi Primary Educational Service Area Office 1, 2) The happiness of working in the school under the Ratchaburi Primary Educational Service Area Office 1 and 3) The relationship between the school administrator's leadership and the happiness of working in the school under Ratchaburi Primary Educational Service Area Office 1 This research is a descriptive research, the sample consisted of 123 schools in Ratchaburi Primary Educational Service Area Office 1, The 2 respondents from each school consisted of a director or a deputy director or a representative and a teacher. The research instrument was a questionnaire. The statistical analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson’s product moment correlation coefficient. The results of this research were as follow: 1) The leadership of school administrators under the Ratchaburi Primary Educational Service Area Office 1, as a whole were a high level, Each aspect was found high level ( = 4.30, S.D. = 0.61), ranking from the highest to the lowest mean: inspire a shared vision, model the way, enable other to act, encourage the heart, and challenge the process. 2) Happiness in working in schools under the Ratchaburi Primary Educational Service Area Office 1, as a whole were a high level ( = 4.32, S.D. = 0.59), ranking from the highest to the lowest mean: Connection, Work Achievement, Recognition, and Love of the Work. And 3) The relationship between the leadership of school administrators and happiness in working in schools under Ratchaburi Primary Educational Service Area Office 1 was found statistically significant at .01 level.